3 Year outcome after treatment of uterovaginal prolapse with a 6-point fixation mesh. (December 2020) - Kuszka, Andrzej; Brandt, Andreas; Niesel, Achim; Lutz, Henrik; Mengel, Mathias; Ulrich, Daniela; Fünfgeld, Christian
Abstract: Introduction: The aim of this study was to describe the intermediate outcome of a single-incision 6-point fixation transvaginal mesh for the treatment of primary and recurrent pelvic organ prolapse (POP). Study design: This was a prospective cohort study including consecutive patients undergoing POP repair with the InGYNious anterior transvaginal mesh. Inclusion criteria were women with symptomatic stage II POP or higher. Exclusion criteria were the unwillingness or inability to give written informed consent, malignant diseases, neuro-muscular disorders, chronic pain syndrome or previous radiation in the pelvis. Every study participant completed a structured questionnaire, a urogynecological examination according to the IUGA-ICS POP-Q staging system and the validated P-QoL questionnaire before the operation and three years postoperatively. Results: 254 patients were included into the study, 179 were available for the three-year follow-up (70 %). Sixteen patients (8.2 %) had undergone reoperation for recurrent or de novo prolapse (12/16 patients underwent reoperation in the posterior compartment) and were excluded from the objective outcome analysis. In the final study group, all POP-Q measurements, urge urinary incontinence and voiding dysfunction were significantly improved. The de novo SUI rate was 27/ 120 (23 %) in women without reoperation for SUI and/ or POP and without primary SUI. No serious adverse events occurred. Four (1.5 %) patients had mesh exposure at the one-year follow-up and been treated with local oestrogen. At three-year follow-up, no new mesh exposure was seen. De novo dyspareunia rate was low (n = 5 (3 %)). Conclusions: In this study, the objective outcome three years after anterior POP repair with the InGYNious transvaginal mesh was good. The reoperation rate both for mesh related problems or prolapse were rare.